The psychopathology of functional somatic syndromes : neurobiology and illness behavior in chronic fatigue syndrome, fibromyalgia, gulf war illness, irritable bowel, and premenstrual dysphoria /: neurobiology and illness behavior in chronic fatigue syndrome, fibromyalgia, gulf war illness, irritable bowel, and premenstrual dysphoria. (2020) - Patarca-Montero, Roberto; Manu, Peter, 1947-
No abstract available